SISTEM PENDUKUNG KEPUTUSAN DALAM PENILAIAN PRESTASI KERJA MENGGUNAKAN FUZZY-AHP DAN SAW - Denni Kurniawan; Catur Nugroho (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2019)
Employee appraisal is one of the company's efforts to evaluate employee performance and productivity. As the result, the company can also give awards to employees who are considered gives high contribution to company.  However, it is not easy to measure employee performance, because most them only based on the leaders valuation which is subjective and do not based on standards. The objective of this study is to develop a system to assess employee performance by using a combination of Fuzzy Logic, Analytic Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods. The AHP is a method of weighting in based on multi-criteria decisions. This method uses a pairwise comparison matrix to  calculate the weight value. The Fuzzy logic is used to overcome the problem, where the AHP method is indicated still have subjectivity in criteria evaluation. After calculation based on combination of Fuzzy-AHP methods, the final result of employee performance will determined by using SAW method. The employee with the highest weight value will considered as the most productive employee and also gives the best performance in the company.